Blended Learning Model to Enhance Managerial Competence: An Islamic Leadership Perspective - Utama, Prasetya; Suciati, Suciati (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2025)
Blended learning enhances managerial competence through a holistic Islamic leadership perspective. The study aims to explore Islamic leadership in blended learning to improve managerial competence and ethical job performance. This study employs a qualitative descriptive approach to analyze the implementation of blended learning in PKA training at BPSDMD NTB. Data collection includes interviews, observations, and document analysis to explore the integration of Islamic leadership principles and their impact on managerial competence. The study found that effective blended learning requires strong participant engagement, reliable technology, interactive facilitation, and flexible scheduling. Key challenges include limited interaction, infrastructure issues, and time management, all affecting the success of managerial training at BPSDMD NTB. This study contributes to the academic discourse by bridging the gap between Islamic leadership and modern educational strategies, offering a model that can be adapted to various public sector training programs. This study concludes that integrating Islamic leadership into blended learning effectively enhances managerial competence, promotes ethical leadership, and supports inclusive, interactive training for public administrators in the digital era.